Partial discharge localization of refined bleached deodorized palm oil (RBDPO) based on acoustic emission method - Ahmad, Nur Darina; Mohd Hashim, Ahmad Hafiz; Azis, Norhafiz; Talib, Mohd Aizam; Md Rezali, Khairil Anas; Nik Ali, N. H.; Jasni, Jasronita; Masahiro, Kozako; Mohd Jamil, Mohamad Kamarol (IEEE, 2023)
This paper examines the performance of partial discharge localization refined bleach deodorized palm oil (RBDPO) based on acoustic emission (AE) partial discharge (PD) method. The PD was initiated through a needle-plane electrodes configuration. The electrical PD was measured through Impedance Matching Circuit (IMC) whereby the AE PD signal was measured using AE sensor placed on the surface of the test tank. The time of arrival (TOA) was computed based on the electrical and AE PD signals. It is found that the PD count and maximum amplitude for RBDPO are lower than mineral oil. The PD in RBDPO can be located through TOA whereby the location error is lower than MO.